The Complex Nature of Integrating Sustainable Development for Mixed Used Buildings in Nepal (International Journal of Innovative Research in Engineering & Management, 2022)
One of the most critical concerns of our  generation is sustainability. This study aims to determine  the extent to which the construction sector in Nepal  considers and applies sustainability concepts in its project  management activities to develop a change strategy to  improve sustainability practices. To better understand the  existing situation, this research was conducted through  semi-structured interviews. First, the existing literature on  sustainability practices was critically studied to  understand the current situation and the participating  company's objective to improve sustainability  performance in developing countries. The literature  review results formed the basis for a series of semi structured interviews with eight members of middle and  senior management representing three different  stakeholder groups: clients, contractors, and regulatory  agencies. The interviews were conducted to gain a deeper  understanding of the reasons behind current practices and  barriers to implementing sustainability in Nepalese  mixed-use buildings. The interview data were coded and  analyzed using the thematic analysis method. The  findings of this research show how difficult it is to  implement sustainability in buildings of Nepal, and the  statistics show that the practices of many organizations  are poor in terms of socio-environmental sustainability.
Keywords: Sustainability; Construction; Environment; Project Management; Implementation; Interpretivism; Inductive; Qualitative; Organization; Mixed-Use Building